Pengaruh Pemberian Oestradiol Benzoat Terhadap Profil Hormon Progresteron Pada Kambing Betina Peranakan Etawah = Effect of Oestradiol Benzoaton the Profile of Progesteron Hormone of Half Breed Etawah Female Goats - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
The aim of this experiment was to determine the effect of oestradiol benzoate on the estrous cycle to the profile of progesterone hormone of half-breed etawah female goats. This experiment used 16 female goats with body weight ranges of 25 -30 kg, and age between 2-3 years old. The animals were devided into 4 groups treatment, (1) control, (2) oestradiol benzoat administration on day 4, (3) oestradiol benzoat on day 10, and (4) oestradiol benzoat administration on day 17 after estrus Data were analyzed based on split plot design with treatments, as the main plot and 5 treatment as the sub plot. Group one, as the control, was injected with diluter estrogen oil, group two injected with oestradiol benzoate 4 days after estrous (metestrous phase), group 3 was injected with oestradiol benzoate 10 days after estrous (diestrous phase) group 4 was injected with oestradiol benzoate was 17 days after estrous (proestrous phase). The injection was carried on in single dose of 75 ug/kg-body weight. The sub plot was blood sample collected in day 2, 6,10,14, and 18, after the experiment goats indicated estrous symptoms. The hormone progesterone concentration in blood samples carried out by using Radioimmunoassay ( RIA ). The result indicated that in group one (control) the lowest profile was on day 2, (6,7+1,0 ng/ml serum), then gradually increased and the highest was accured on day 14 (15,7 ±7,8 ng/ml serum) and then it decreased on day 18 (8,3+1,2 ng/ml serum) after estrous. The addition of oestradiol benzoate in every phase after estrous indicated, that the estrous symptom occured after 2 days later. In the second group indicated that hormone progesterone profile on day 2 (12,1+3,7 ng/ml serum), followed by the increased and the heighest (22,0+8,6 ng/ml serum) and this decreased lower to 18 days (13,0± 6,2 ng/ml serum) after estrous. In group 3 profile of progesterone hormone indicated that on day 2 relatively neigner, (14,4+ 6,0 ng/ml serum) and then decreased gradually until day 10 (12,6+3,9 ng/ml serum), then it increased again on day 18'(13,7+8,6'ng/ml serum) after estrous. In group 4 the profile of progesterone hormone in day 2 (3,8±2,8 ng/ml serum) then gradually increasing until it reached peak at 14 days (15,2+11,3 ng/ml serum), then decreased on 18 days (3,8 + 2,4 ng/ml serum) after estrous. Statistically, hormone concentration of progesterone on the treatment groups were no significant, (P > 0,05). However in sample collection was significant (P < 0,05). The conclusion of this experiment was that was the hormone profile of progesterone in control group was significantly different with treatment, metestrous phase, and diestrous but no significant with group treatment in proestrous phase